2017
DOI: 10.1371/journal.pone.0188182
|View full text |Cite
|
Sign up to set email alerts
|

Climate change mitigation opportunities based on carbon footprint estimates of dietary patterns in Peru

Abstract: Food consumption accounts for an important proportion of the world GHG emissions per capita. Previous studies have delved into the nature of dietary patterns, showing that GHG reductions can be achieved in diets if certain foods are consumed rather than other, more GHG intensive products. For instance, vegetarian and low-meat diets have proved to be less carbon intensive than diets that are based on ruminant meat. These environmental patterns, increasingly analyzed in developed nations, are yet to be assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 54 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…To do so, Scopus, Web of Knowledge (ISI) and Google scholar have been managed considering only English language peer-review studies. According to it, although more than 50 studies have been found assessing environmental impacts of country diets, in total 21 peer-review studies (Wallén et al, 2004;Risku-Norja et al, 2009;Muñoz et al, 2010;Pathak et al, 2010;Tukker et al, 2011;Vieux et al, 2012;Meier and Christen, 2013;Sáez-Almendros et al, 2013;Saxe et al, 2013;Vieux et al, 2013;Werner et al, 2013;Wilson et al, 2013;Scarborough et al, 2014;van Dooren et al, 2014;Röös et al, 2015;van Dooren et al, 2016;Castañé and Antón, 2017;Pairotti et al, 2017;Vázquez-Rowe et al, 2017;Esteve-Llorens et al, 2018;van de Kamp et al, 2018) have been identified fulfilling the selection criteria.…”
Section: Literature Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, Scopus, Web of Knowledge (ISI) and Google scholar have been managed considering only English language peer-review studies. According to it, although more than 50 studies have been found assessing environmental impacts of country diets, in total 21 peer-review studies (Wallén et al, 2004;Risku-Norja et al, 2009;Muñoz et al, 2010;Pathak et al, 2010;Tukker et al, 2011;Vieux et al, 2012;Meier and Christen, 2013;Sáez-Almendros et al, 2013;Saxe et al, 2013;Vieux et al, 2013;Werner et al, 2013;Wilson et al, 2013;Scarborough et al, 2014;van Dooren et al, 2014;Röös et al, 2015;van Dooren et al, 2016;Castañé and Antón, 2017;Pairotti et al, 2017;Vázquez-Rowe et al, 2017;Esteve-Llorens et al, 2018;van de Kamp et al, 2018) have been identified fulfilling the selection criteria.…”
Section: Literature Search Strategymentioning
confidence: 99%
“…It is important to take in mind that the number of calories that an average person needs daily depends on several factors, such as the minimum and average dietary energy requirements (Vázquez-Rowe et al, 2017), level of activity, gender, age, weight, geographical location and cultural issues (EFSA, 2009). The carbon footprint has been considered as a proxy for environmental impact in line with the studies checked and taking into consideration the awareness from the research community and society on the reduction of GHGs emission and counteracting the climate change effects.…”
Section: Introductionmentioning
confidence: 99%
“…The State of Food Security and Nutrition in the World 2020 [1] declared that the impact of a shift to dietary guidelines, stratified by socioeconomic subgroups [17]. Researchers in Peru modeled the environmental impacts of several dietary patterns using individual dietary data and explored heterogeneity by socioeconomic status and education level [19]. An improved understanding of the complex relationship between different geographies and socio-demographic strata is warranted to identify leverage points for promoting sustainable food programming and policy in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…We base our calculations on the data and methodology presented in previous sections. The total protein intake coming from meat and dairy is 62.8 g / person / day 100 . The carbon footprint of the diet is /year 101 .…”
Section: Carbon Impact Of Different Diets Containing Meat and Dairymentioning
confidence: 99%